2020
DOI: 10.1155/2020/9123281
|View full text |Cite
|
Sign up to set email alerts
|

Copper Does Not Induce Tenogenic Differentiation but Promotes Migration and Increases Lysyl Oxidase Activity in Adipose-Derived Mesenchymal Stromal Cells

Abstract: Background. Copper belongs to the essential trace metals that play a key role in the course of cellular processes maintaining the whole body’s homeostasis. As there is a growing interest in transplanting mesenchymal stromal cells (MSCs) into the site of injury to improve the regeneration of damaged tendons, the purpose of the study was to verify whether copper supplementation may have a positive effect on the properties of human adipose tissue-derived MSCs (hASCs) which potentially can contribute to improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…We conclude that ASCs are highly sensitive towards the CuO NPs incorporated in the nanocomposite. It has been reported that after a 5-day exposition to 25 μm CuSO 4 , cellular respiration of human ASCs was decreased as well as gene expression of collagen I [ 62 ], supporting our determination of lower ECM formation in the 5 w/w % CuO containing material compared to the control.…”
Section: Discussionsupporting
confidence: 90%
“…We conclude that ASCs are highly sensitive towards the CuO NPs incorporated in the nanocomposite. It has been reported that after a 5-day exposition to 25 μm CuSO 4 , cellular respiration of human ASCs was decreased as well as gene expression of collagen I [ 62 ], supporting our determination of lower ECM formation in the 5 w/w % CuO containing material compared to the control.…”
Section: Discussionsupporting
confidence: 90%
“…We propose that Atp7a-mediated transient Cu deficit is beneficial for initiation of lipogenesis and lipid accumulation, and serves as an integral component of the entire differentiation program. The effects of Cu on cytoskeleton and cell morphology were previously observed in 3T3-L1 cells [ 23 ], as well as in other cell types [ 32 , 33 ]. Our studies suggest that β-catenin, which coordinates gene transcription and cell adhesion, could be an important factor in the observed morphological changes; however, the role of Cu in adipocyte morphology need to be studied further.…”
Section: Discussionmentioning
confidence: 91%
“…However, the cuproptosis level of the TDSC-7 cluster cells was abnormally decreased, indicating that these cells were in a precarious state. Copper is an essential trace metal, and proper copper supplementation has a beneficial effect on tendon regeneration and self-renewal ( 39 ). Herchenhan et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cuproptosis level of the TDSC-7 cluster cells was abnormally decreased, indicating that these cells were in a precarious state. Copper is an essential trace metal, and proper copper supplementation has a beneficial effect on tendon regeneration and self-renewal (39). Herchenhan et al found that an appropriate copper concentration was crucial for maintaining lysyl oxidase activity, which was required for orderly collagen fibril formation in tenocytes (40).…”
Section: Discussionmentioning
confidence: 99%